Emery, Louise (audio interview #4 of 4) - Emery, Louise (b. 1/00/1897 - d. 3/1/1985); Shirey, Robin, interviewer
INTERVIEW DESCRIPTION - This last interview with Louise Emery focuses primarily on her post-retirement trip around the world. Like the previous ones, this interview was recorded in her living quarters at Pilgrim's Place. The audio quality is good. 3/11/1977